The effect of aerobic exercise on occupational stress of female nurses: A controlled clinical trial - Zinat Mohebb; Setareh Fazel Dehkordi; Farkhondeh Sharif; Ebrahim Banitalebi (Universidad de Antioquia, 2019)
Objective. This work sought to determine the effectiveness of an aerobic exercise program on the occupational stress of nurses. Methods. Prevention-type controlled clinical trial carried out with the participation of 60 nurses working in hospitals affiliated to Shahrekord University of Medical Sciences in Iran. Randomly, the nurses were assigned to the experimental group or to the control group. The intervention consisted in an aerobic exercise program lasting three months with three weekly sessions one hour each. The Health and Safety Executive (HSE) questionnaire measured occupational stress with 35 questions, each with five Likert-type response options, which can have a maximum score of 175 points; higher scores meant lower levels of occupational stress. The HSE was evaluated during three moments: upon registering, after finishing the exercise program (week 8), and two months after terminating the intervention (week 16). Results. The level of occupational stress was the same in the experimental and control groups during registration (86.2 vs. 86.3). Upon finishing the aerobic exercise program (week 8), the experimental group showed a higher score than the control group (119.7 vs. 86.2, p<0.01), with this score diminishing after two months of having ended the intervention (91.4 vs. 85.8, p=0.061). Conclusion. The aerobic exercise program was associated to decreased work stress of nurses in the experimental group compared to the control group at eight weeks, but this difference did not persist when the experimental group did not continue with the program.   How to cite this article: Zinat Mohebbi Z, Dehkordi SF, Sharif S, Banitalebi E. The Effect of Aerobic Exercise on Occupational Stress of Female Nurses: A Controlled Clinical Trial. Invest. Educ. Enferm. 2019; 37(2):e05.